Towards a co-creative stakeholder engagement in Smart City projects: a life-cycle approach. - Ehwi, Richmond Juvenile; Holmes, Hannah; Maslova, Sabina; Burgess, Gemma (Innovation: The European Journal of Social Sciences, 2023)
Engaging stakeholders to co-create Smart Cities is an aspiration for many city governments. However, existing stakeholder engagement frameworks tend to be technologically deterministic from the outset, leaving no room for meaningful co-creation. This paper proposes a framework for engaging stakeholders in Smart City development without presuming an already existing technology which stakeholders must accept. The framework follows the life-cycle approach to disaggregate the Smart City development process into seven separate but interrelated stages anchored on three pillars – 'the right to the city', 'the IAP2 spectrum of public participation' and 'technological sovereignty' to highlight issues deemed critical for a meaningful co-creative stakeholder engagement. The study identifies funding, an understanding of the city and its challenges from multiple stakeholder perspectives, the promotion of digital rights, and meaningful stakeholder engagement as four pertinent issues that must be taken on board to move this framework from a conceptual abstraction to a practical toolkit.